PEMAHAMAN GURU TERHADAP SISTEM PENILAIAN AUTENTIK PADA MATA PELAJARAN IPS DI SMP NEGERI SE-KABUPATEN OGAN ILIR - Intan Rara Sinta; M. Djahir Basir; Fitriyanti Fitriyanti (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
This research discusses about the understanding of authentic assessment on social studies in Junior High School Ogan Ilir. The formulation of the problem is how the understanding of teachers in plan, execute, and report on authentic assessment system on social studies in Junior High School Ogan Ilir. The variables of this research is the understanding of teachers to authentic assessment. This research uses qualitative method. The subjects were teachers grade VII and VIII on Junior High School Ogan Ilir, which using curriculum 2013 totaled 10 social studies teachers. Data were collected through interviews and documentation techniques. Data obtain using triangulation tested. The result show that understanding authentic teachers in step (1) planning assessment, teachers entered good categories with an average score of 79,34, phase (2) the implementation of the assessment, the teachers entered good categories with an average score of 71,11 %, and a stage (3) assessment report, the teachers entered into very good understanding of the categories with an average score of 86%. Teachers should always be given about authentic assessment system, then the assessment is made simpler for easy to used and applied by teachers.